Pemberian Karang Memadu Sebagai Sanksi Adat Untuk Mencegah Poligami di Desa Adat Panglipuran - I Nyoman Putu Budiartha; I Wayan Suka Wirawan; I Nyoman Srimurti (Kertha Wicaksana, 2021)
The granting of land "Tanah Karang Memadu" for those conducting polygamous marriages in Pengelipuran Traditional Village, Bangli is a form of customary sanction from local wisdom that must be preserved. This customary sanction has proven able to prevent the community's intention to practice polygamy. In Law Number 1 of 1974 which has been amended by Law Number 16 of 2019 concerning Marriage, it is emphasized that marriage is a physical and spiritual bond between a man and a woman. So the principle adopted is the principle of monogamy. However, many people for some reason have polygamous marriages or have more than one wife. Normatively, the adat community of Penglipuran Village views polygamy as a violation of customary norms. That is why those who dare to practice polygamy will be sanctioned to leave the village yard and then be given a place known as "Karang Mamadu". This research answers the problem, how is the implementation of Karang Memadu customary sanctions in Penglipuran Village, and whether the Karang Memadu customary sanctions are implemented effectively in Penglipuran Traditional Village. This type of research will be used in this type of empirical legal research. The findings of the research confirm that the provision of "Karang Memadu" is a form of customary sanction which has very significant legal implications in preventing the occurrence of polygamous or "Memadu" marriages. The indication is, until this research has been completed, the "Karang Memadu" in question has never been used by those who carry out polygamous marriages. Suggestions that can be recommended are, the sanction of giving this "Karang Memadu" is so that it is preserved to ensure social order .